A call to promote healthcare justice: A summary of integrated outpatient clinics exemplifying principles of Catholic social teaching - Waters, Nicole P. (Linacre Q, 2017)
There is an urgent need to promote healthcare justice for patients as well as members of the healthcare team including physicians. In this article, we explain how principles of Catholic social teaching (i.e., dignity of the individual, common good, destination of goods, solidarity, and subsidiarity) are applied to health care, by featuring various types of outpatient clinics including free, charitable–direct primary care, hybrid, federally qualified health center, and rural health clinic. We describe how attempts have been made to improve the quality and access of health care by creating new medical schools (i.e., Marian University College of Osteopathic Medicine) and training programs as well as allocating government funding to alleviate the cost of training new healthcare providers through the National Health Service Corps. Finally, we suggest a few approaches (i.e., adopting new clinic models to include volunteer healthcare professionals and cross-training members of the healthcare team) to fill in current gaps in health care. Summary: There is a need to promote justice in healthcare. In this article, we explain how principles of Catholic social teaching are applied to health care. To illustrate this, we feature various types of outpatient clinics. We also describe how attempts have been made to improve the quality and access of health care. Finally, we suggest further ways to improve healthcare reform based upon Catholic social teaching.